Non-farm enterprises and poverty reduction amongst households in rural Nigeria: a propensity score matching approach - Shehu, Abdulaziz; Ahmad Siddique, Shaufique Fahmi (International Organization Of Scientific Research, 2014)
The data of nationally representative household survey from rural Nigeria was used to examine the effect of non-farm enterprise activities on improvement in the welfare of households in rural Nigeria, using total annual household consumption expenditure as a measure of their welfare. Propensity score matching approach was used for the analysis, and the result shows that rural households that engage in non-farm enterprise activities are having higher consumption expenditure than those that did not diversify into such activities. This suggests that, non-farm enterprises could be a pathway for improving the wellbeing of rural households in Nigeria and in the remaining sub-Saharan African countries.